PENGARUH KETERLIBATAN KARYAWAN, BUDAYA ORGANISASI DAN DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BHANDA GHARA REKSA (PERSERO) CABANG PALEMBANG - Yunidar Erlina; Kamariah Kamariah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
This study aims to determine whether there is a significant effect of employee involvement, organizational culture and organizational support on employee performance at PT. Bhanda Ghara Reksa (Persero) Palembang Branch. The sample in this study were 32 respondents. The types of data in this study are primary data and secondary data. The primary data obtained by the authors by distributing questionnaires to respondents, by conducting validity and reliability tests. While the hypothesis test is done with the F test and t test. Based on the F test or simultaneous test of Employee Engagement, Organizational Culture and Organizational Support have a positive and significant effect on Employee Performance at PT. Bhanda Ghara Reksa (Persero) Palembang Branch with a value of 15.135 with a significance of 0.000. Based on the results of data processing with SPSS 16 on the t-test of Employee Involvement, it was obtained tcount of 5.052 with a significance of 0.000, Organizational Culture obtained tcount of 4.269 with a significance of 0.000 and Organizational Support obtained tcount of 3.383 with a significant 0.002.Keywords: Employee Engagement, Organizational Culture, Organizational Support and Employee Performance